Memory analysis ofmicrocontroller programs - Boyka, M. (БГАТУ, 2021)
Program memory. One of the types of non-volatile memory is usually used to store programs: ROM (disposable software ROM), EPROM (electrically programmable ROM with ultraviolet erasure), EERROM (ROM with electric recording and erasure, this type also includes modern Flash-memory chips' or ROM (reusable ROM).
Keywords: program memory; store program code; data memory; modern Flash-memory chips